En berättelse om statare: Framställningar i tidskriften Lantarbetaren 1933 – 1949 - Aspelin,Ylva (2024)
A historical narrative of statare: Portrayals in the trade union paper Lantarbetaren In Sweden, a system of married agricultural contract workers paid in kind, known as statarsystemet, persisted until the mid-20th century. These workers (statare) are understood as a highly socially vulnerable group in Swedish history, portrayed in fictional literature as well as in TV series. This thesis addresses the agrarian trade union movement and how statare were perceived and portrayed by their contemporaries. The purpose is to examine the trade union paper Lantarbetaren to reconstruct the historical narrative created regarding statare in the journal throughout the 1930s and 1940s. Using Jörn Rüsen's concept of historical narrative combined with Ernesto Laclau and Chantal Mouffe's concepts of moments, elements, and nodal points, this thesis aims to illuminate the dynamics of the final decades of the system's existence and the gradual development and significance of the union paper's historical narrative. The main argument concludes that the editorial staff, writers, and readers of Lantarbetaren, over the course of sixteen years, constructed a historical narrative regarding statare that was shaped through the inclusion, exclusion, and definition of various specific topics, ideas, and words. Among the inclusions, the thesis argues, was the idea of organizing oneself to achieve inner prosperity, a certain self-cultivation through reading, and an intellectualization of agrarian work. Among the exclusions were the active rejection of Christian values and criticism against the author Ivar Lo-Johansson. The historical narrative was also defined by the characterization of the term statare in relation to the broader term lantarbetare.
Keywords: Statare; Lantarbetare; Lantarbetaren; Statarsystemet; Agricultural workers; Jörn Rüsen; Historical narrative